Differential habitat use by demographic groups of the redfinger rubble crab Eriphia gonagra (Fabricius, 1781) - Andrade, Luciana Segura de [UNESP]; Góes, João Marcos; Fransozo, Vivian; Alves, Douglas Fernandes Rodrigues [UNESP]; Teixeira, Gustavo Monteiro; Fransozo, Adilson [UNESP] (Int Inst Ecology, 2014)
The structurally diverse rocky shores along the northern coast of the state of Sao Paulo, Brazil, support a varied fauna and provide refuges for many organisms. Some of these environments allow for extensive microhabitats, among them the sand reefs formed by the polychaete Phragmatopoma lapidosa, which occupy much of this area. The beauty of the landscape attracts large numbers of tourists, who contribute to the damage to the sand reef colonies, causing an imbalance in the patterns of population distribution and of this ecosystem. We describe the structure and population biology of the redfinger rubble crab Eriphia gonagra, and investigated the differential occupation of the habitat by each demographic category of this species. Crabs were sampled monthly for two consecutive years on the rocky coast of Grande Beach, Ubatuba, Sao Paulo, during spring low tides. Sampling was carried out over an area of approximately 1200 m(2), during two hours on the rock surface and another two hours on the sand reefs. A total of 1407 crabs were collected; 776 on the sand reef (SR) and 631 on the rocky shore (RO). The majority of juvenile crabs inhabited the SR, while adult crabs were equally distributed in both microhabitats. This study showed that the SR is a natural nursery ground for the establishment of the early juvenile stages of E. gonagra, which use the reefs as a refuge and food resource. Many other organisms (mollusks, echinoderms, polychaetes etc.) settle on the reefs, and these areas may be among the most important in maintaining benthic diversity in the region.

Os costões rochosos do litoral norte paulista, devido à sua constituição diversificada, sustentam uma grande diversidade de espécies animais e vegetais, além de proporcionar uma série de abrigos para proteção de muitos organismos. Em alguns destes costões ocorre a formação de microhabitats, entre eles os recifes de areia formadas pelo poliqueta Phragmatopoma lapidosa, que ocupam grande parte desta área. A paisagem diferenciada do local atrai um grande número de turistas, o que contribui para a deterioração das colônias que constituem esse recife, causando um desequilíbrio nos padrões de distribuição das populações desse ecossistema. Este trabalho visou levantar informações sobre a estrutura e dinâmica populacional de Eriphia gonagra, além de investigar uma ocupação diferencial do habitat por diferentes grupos etários deste caranguejo. Os caranguejos foram amostrados mensalmente, durante dois anos consecutivos, no costão rochoso da Praia Grande, Ubatuba, São Paulo, Brasil, em períodos de marés baixas de sizígia. A coleta ativa dos indivíduos foi efetuada em uma área de aproximadamente 1200 m2 por um período de duas horas na superfície rochosa e outras duas horas nos recifes de areia. Foi capturado um total de 1407 indivíduos, sendo 776 no recife de areia (SR) e 631 na superfície rochosa (RO). A maior parte dos jovens habita o recife, enquanto adultos encontram-se igualmente distribuídos nas duas áreas amostradas. Este estudo mostra que os recifes de areia podem ser considerados berçários de suma importância para o estabelecimento dos estágios juvenis de E. gonagra, que utilizam tais locais para proteção e alimentação. Muitos outros organismos (moluscos, equinodermos, poliquetas etc) se estabelecem sobre os recifes, sendo que essas áreas podem estar entre as mais importantes na manutenção da diversidade bêntica na região.
Ocupação diferencial do habitat por grupos demográficos do caranguejo de dedos vermelhos Eriphia gonagra (Fabricius, 1781)
Keywords: Coastal structures; Crab nursery; Ecological zonation; Xanthoidea; Ontogenetic habitat shift; Estrutura costeira; Berçário de caranguejos; Zonação ecológica; Xanthoidea; Mudança de habitat na ontogênese